2014
DOI: 10.1016/j.vaccine.2013.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Towards a safe and effective chlamydial vaccine: Lessons from the eye

Abstract: HighlightsChlamydia trachomatis is the leading infectious cause of blindness.Vaccine trials against ocular C. trachomatis infection were conducted in the 1960s.Whole organism vaccines induced short-lived, strain-specific protective immunity.Many correlates of protective immunity and pathology have been defined.Important lessons have been learned to inform the development of a chlamydial vaccine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
42
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 96 publications
1
42
0
Order By: Relevance
“…Of concern, C. trachomatis infection in some primates resulted in more severe disease with worse inflammation post-vaccination demonstrating a role for incomplete immunity in enhanced inflammatory pathology [9,10]. However a critical analysis of human trachoma vaccine trials failed to demonstrate similar vaccine immunopathology in humans [11]. Nonetheless concern about exacerbated inflammatory pathology in previously vaccinated non-human primates has continued to be a barrier that impedes human Chlamydia vaccine trial research.…”
mentioning
confidence: 99%
“…Of concern, C. trachomatis infection in some primates resulted in more severe disease with worse inflammation post-vaccination demonstrating a role for incomplete immunity in enhanced inflammatory pathology [9,10]. However a critical analysis of human trachoma vaccine trials failed to demonstrate similar vaccine immunopathology in humans [11]. Nonetheless concern about exacerbated inflammatory pathology in previously vaccinated non-human primates has continued to be a barrier that impedes human Chlamydia vaccine trial research.…”
mentioning
confidence: 99%
“…The trachoma vaccine trials were conducted using whole inactivated C. trachomatis elementary body (EB) preparations, which induced only partial and short-lived protection against infection (5). Importantly, these studies also reported evidence of disease exacerbation, likely due to immunemediated inflammation and tissue damage (6). These deleterious responses could not be unequivocally recapitulated in subsequent nonhuman primate studies (7).…”
mentioning
confidence: 99%
“…121 Finally, as noted by Mabey et al, "an important difference between ocular and genital infection is that in the eye the damaging sequelae occur at the site of infection, the conjunctival epithelium" while "by contrast in the female genital tract, the major sequelae develop in the fallopian tubes and not at the cervix, which is the site of inoculation". 80 Nevertheless, the pathology of C. trachomatis infection is similar in the eye and genital tract and involves a complex interaction of innate and adaptive immune responses to the organism that influence both protection and pathology in ocular and sexually transmitted chlamydial infections. Vaccine efforts against this intracellular pathogen will need to ensure that any immune responses generated by the ocular and genital vaccines will include the appropriate populations of innate, B, and T-cells that will engender protection and minimize pathology in the host.…”
Section: Acquired Immunity and Pathologymentioning
confidence: 99%
“…Several of these newly characterized virulence targets are being evaluated as potential vaccine candidates. 80 While the chlamydial genetic toolbox has expanded significantly over the past few years, it is likely to continue to become easier and easier to manipulate Chlamydia, with both forward and reverse genetics now being possible (eg, targetron approach), and more advanced techniques such as conditional gene silencing and transposon mutagenesis not far off.…”
Section: The Choice Of Immunogenic Target Antigens Is Rapidly Expandingmentioning
confidence: 99%
See 1 more Smart Citation